Delphi a history of the center of the ancient world - Scott, Michael 1981- (Princeton University Press, 2014)
The oracle and sanctuary of the Greek god Apollo at Delphi were known as the "omphalos"--The "center" or "navel" - of the ancient world for more than 1000 years. Individuals, city leaders, and kings came from all over the Mediterranean and beyond to consult Delphi's oracular priestess; to set up monuments to the gods in gold, ivory, bronze, marble, and stone; and to take part in athletic and musical competitions. This book provides the first comprehensive narrative history of this extraordinary sanctuary and city, from its founding to its modern rediscovery, to show more clearly than ever before why Delphi was one of the most important places in the ancient world for so long. In this richly illustrated account, Michael Scott covers the whole history and nature of Delphi, from the literary and archaeological evidence surrounding the site, to its rise as a center of worship with a wide variety of religious practices, to the constant appeal of the oracle despite her cryptic prophecies. He describes how Delphi became a contested sacred site for Greeks and Romans and a storehouse for the treasures of rival city-states and foreign kings. He also examines the eventual decline of the site and how its meaning and importance have continued to be reshaped right up to the present. Finally, for the modern visitor to Delphi, he includes a brief guide that highlights key things to see and little-known treasures. A unique window into the center of the ancient world, this book will appeal to general readers, tourists, students, and specialists.